The Role of the Madrasah Head as Leader of the Educational Institution at MTs YP. Ummul Quraa Tembung, District. Percut Sei Tuan, Deli Serdang Regency, North Sumatra - Fatin Syahirah; Makmur Syukri (Manajia: Journal of Education and Management, 2024)
The aim of this research is to explain the role of the headmaster as an educational leader in MTs Yp. Ummul Quraa, the method used in this research is descriptive qualitative research method. Data were obtained through interviews, observations, and documentation. The findings of this research emphasize the importance of the headmaster in providing effective leadership, formulating a clear vision, mission, and goals, as well as planning educational activities in accordance with Islamic values. Leadership strategies include selecting qualified students and teachers, using innovative teaching methods, developing relevant curriculum, and conducting regular monitoring and evaluation of educational outcomes. The essence of headmaster leadership involves comprehensive management, positive influence on individuals and groups, and building good relationships with relevant stakeholders. These findings provide a deeper understanding of the role, strategies, and essence of headmaster leadership in improving the quality of education in MTs Yp. Ummul Quraa.